2014
DOI: 10.12982/cmujns.2014.0053
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antioxidant activities, Anthocyanins, Total Phenolic Content, Vitamin C Content and Cytotoxicity of Carissa carandas Linn.

Abstract: Carissa carandas, commonly known in Thai as 'nham-daeng', has a long history in alternative medicine in Thailand. Ethanolic extracts of fresh leaves, unripe fruits and fully-ripe fruits were investigated for their antioxidant activity, total phenolic content, total anthocyanins, anthocyanin identification, vitamin C content and cytotoxicity. Results showed that the leaf extract exhibited the highest antioxidant activity, FRAP value and total phenolic content. The antioxidant activities of leaf, unripe and full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
3
4
0
Order By: Relevance
“…[2] Hence, there were concluded that cytotoxicity of leaf extract was highest at 100 µg/ml, however, fruits (unripe and ripe) were lack of cytotoxicity to inhibit HepG2 cells at same concentration and when increase the dose of assay up to 200 µg/ml. [22] There may imply that KD and KM had no cytotoxic effect with normal cells same concentration as previous reports (100 µg/ml); however, there may be cytotoxic when increase the concentration of extract. Thus, further studies will be conducted to determine the response of normal cells, as well as cell line, with higher concentrations of the extract should be considered.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…[2] Hence, there were concluded that cytotoxicity of leaf extract was highest at 100 µg/ml, however, fruits (unripe and ripe) were lack of cytotoxicity to inhibit HepG2 cells at same concentration and when increase the dose of assay up to 200 µg/ml. [22] There may imply that KD and KM had no cytotoxic effect with normal cells same concentration as previous reports (100 µg/ml); however, there may be cytotoxic when increase the concentration of extract. Thus, further studies will be conducted to determine the response of normal cells, as well as cell line, with higher concentrations of the extract should be considered.…”
Section: Discussionsupporting
confidence: 52%
“…[21] In case of antimicrobial activities, this study was showed positive results of KD and KM along with six bacteria at MIC = 12.5-50 mg/ml, which was corresponded to the previous study was reported antibacterial activities of Karanda fruit extracted by ethanol, which revealed antimicrobial activities against S. aureus (ATCC 2593) and E. coli (ATCC 8739). [13] The previous studies were revealed for cytotoxicity of unripe fruits, fully-ripe fruits and leaves of Karanda extracts (40% of ethanol) were inhibited HepG2 cells [22] and cytotoxicity of leaf extract was inhibit the proliferation of human cervical cancer cells (HeLa), prostate cancer cells (PC-3), and normal mouse fibroblasts (3T3). [2] Hence, there were concluded that cytotoxicity of leaf extract was highest at 100 µg/ml, however, fruits (unripe and ripe) were lack of cytotoxicity to inhibit HepG2 cells at same concentration and when increase the dose of assay up to 200 µg/ml.…”
Section: Discussionmentioning
confidence: 99%
“…This difference might be attributed to the ripening stage or geographical variation [33,34]. On the other hand, phenolic content of the ethanolic extract of leaf, unripe and fully-ripe fruit extracts of C. carandas were 24.91±0.22, 1.29±0.16 and 4.67±0.41 mg GAE/g as found by Pewlong et al [21] which was 533±25 mg GAE/100 g in this study. Sarma et al [20] found 188.75 ± 1.42 μg GAE/g) phenolic content in the methanolic extract of C. carandas (841±65 mg GAE/100 g in this study).…”
Section: Total Phenolic Contentsupporting
confidence: 55%
“…The fruits, leaves, barks, and roots of C. carandas have been used in the treatment of human diseases, such as anorexia, intermittent fever, diarrhea, stomachic, syphilitic pain, burning sensation, mouth ulcer and sore throat, scabies, and epilepsy [18]. There are several studies on the phenolic content and antioxidative activities of C. carandas using absolute methanol [19], 70% methanol [20], 40% ethanol [21] and 80% acetone (for phenolic content) and methanol (for DPPH radical scavenging assay) [22]. To our knowledge, study on the effect of solvent in the phenolic compound extraction and antioxidant activity of these two fruits has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…It contains a huge amount of vitamins, phenolics, minerals (5)(6)(7). It has been used as folk medicine with various therapeutic properties like antidiabetic, antimicrobial, cytotoxicity, hepatoprotective, anti-inflammatory (8)(9)(10)(11)(12). It's commonly converted to jam, jellies and pickles (13).…”
Section: Introductionmentioning
confidence: 99%